2022
DOI: 10.1093/ajcn/nqac073
|View full text |Cite
|
Sign up to set email alerts
|

Ultraprocessed food consumption and kidney function decline in a population-based cohort in the Netherlands

Abstract: Background Ultra-processing makes food products more convenient, appealing, and profitable. Recent studies show that high ultra-processed food (UPF) intake is associated with the cardio-metabolic disease. Objectives The aim of this study is to investigate the association between UPF consumption and risk of kidney function decline in the general population. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…33,34 The positive association that we observed between N2, N2-dimethylguanosine and ultra-processed foods and between N2, N2-dimethylguanosine and CKD risk was consistent with our hypothesis given our previous study demonstrating that higher ultra-processed food was associated with higher risk of incident CKD. 4 N2, N2dimethylguanosine is a product of transfer ribonucleic acid (tRNA) degradation, and its serum level reflects the rate of tRNA turnover and renal clearance. The circulating level of tRNA degradation products is a marker of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33,34 The positive association that we observed between N2, N2-dimethylguanosine and ultra-processed foods and between N2, N2-dimethylguanosine and CKD risk was consistent with our hypothesis given our previous study demonstrating that higher ultra-processed food was associated with higher risk of incident CKD. 4 N2, N2dimethylguanosine is a product of transfer ribonucleic acid (tRNA) degradation, and its serum level reflects the rate of tRNA turnover and renal clearance. The circulating level of tRNA degradation products is a marker of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Higher ultra-processed food consumption was associated with adverse kidney outcomes in the Atherosclerosis Risk in Communities (ARIC) study conducted in middle-aged adults in the United States, 2 older adults in Spain, 3 and in a northern Netherlands population. 4 The mechanism underlying the association between ultra-processed foods and CKD is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…During the COVID-19 pandemic, adolescents reported an increase in screen time and changes in eating habits ( 3 , 5 ), such as eating more frequently in front of the TV and snacking, habits that were associated with increased consumption of UPR foods during the pandemic in the general population ( 33 ). This can be worrisome for adolescents with chronic conditions, since increases in UPR food consumption have been associated with a worse prognosis of the underlying disease and increased risk of kidney function decline in the general population ( 34 ), and increased risk of cardiovascular ( 35 ) and inflammatory bowel disease ( 36 ) in adults with clinical conditions. In the current study, however, adolescents with chronic conditions showed an improved dietary pattern compared to healthy peers.…”
Section: Discussionmentioning
confidence: 99%
“…Another general population-based cohort from Netherlands of 78 346 participants free of chronic kidney disease at baseline showed that on average, 37.7% of total food intake came from ultraprocessed foods. Higher ultraprocessed food consumption was associated with a higher risk of a composite kidney outcome (incident chronic kidney disease or ≥30% eGFR decline) and a more rapid eGFR decline, independent of confounders and other dietary indices [61].…”
Section: Avoid Ultraprocessed Foodsmentioning
confidence: 91%